If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6q-348=6(2-5q)-4q
We move all terms to the left:
6q-348-(6(2-5q)-4q)=0
We add all the numbers together, and all the variables
6q-(6(-5q+2)-4q)-348=0
We calculate terms in parentheses: -(6(-5q+2)-4q), so:We get rid of parentheses
6(-5q+2)-4q
We add all the numbers together, and all the variables
-4q+6(-5q+2)
We multiply parentheses
-4q-30q+12
We add all the numbers together, and all the variables
-34q+12
Back to the equation:
-(-34q+12)
6q+34q-12-348=0
We add all the numbers together, and all the variables
40q-360=0
We move all terms containing q to the left, all other terms to the right
40q=360
q=360/40
q=9
| 3x+7(-7x-20)=90 | | 3(d-6)=3 | | (-1+8x)+46=18x+5 | | r-11÷11=-10÷11 | | 7(1+x)=6(5+x) | | 28x^2+24x+9=0 | | -17+13x=13x-17 | | c=5/9-(F-32) | | 1/9w-6=7/9 | | 7x+20=0 | | -7x+3(3x-7)=3 | | 5-3x=x+11 | | 13x-29=7 | | 9/5y=-10 | | 7x-7=-3x-7 | | d-12=19d-12=19 | | 18x+3=3(6x-12) | | -2(6y-2)+9y=1+3(2y-1) | | -8(3x-1÷4)=2(9-7x) | | 5(4-2x)=8 | | 46=9r-8 | | -4(-4x-6)-7x=6(2x+7) | | –12x+4=–32 | | -3(6x-4)+6x=-3(x+1) | | -2/5×y=4 | | 7a+5=47 | | -6(y-7)=-5y-5 | | 5x-45=x+15 | | 3(x+12-5)x=22 | | 7(w-1)-9=-2(-9w+9)-7w | | P(n)=0.8n+5.50 | | 14=7m/8 |